Using Forum Theater as a Teaching Tool to Combat Patient Bias Directed Toward Health Care Professionals - Nina Rizk; Shaunpaul Jones; Margie Hodges Shaw; Adrienne Morgan (Association of American Medical Colleges, 2020)
Introduction Health care professionals who identify as members of underrepresented and racial minority groups may experience bias from patients and patient families. These occurrences disrupt the educational and therapeutic environments, distress the targeted individuals and allies, and create potential legal liability. Yet there are few educational opportunities for individuals to brainstorm and implement strategies for responding professionally during such instances. Methods Presented first as a grand rounds, then an invited workshop, and finally an invited series, this educational activity was developed in a stepwise manner over the course of a year. Each format was sequentially modified based on feedback from participants-more than 200 physicians and other health care professionals-using evaluation forms that were voluntary and anonymous. The educational activity used an adaptation of forum theater, in which participants role-played an instance of oppression with a goal of altering the ultimate outcome. This approach provided participants with the opportunity to develop and rehearse responses to workplace bias in a way that preserved the provider-patient relationship. Results Feedback for these educational sessions was overwhelmingly positive. Participants noted the importance of acknowledging and addressing bias in the workplace and encouraged facilitators to expand the sessions in length, frequency, and scope. Discussion Forum theater is a methodology that can be employed in health care to teach appropriate and authentic responses to expressed patient bias while maintaining the therapeutic relationship. The positive reception from participants in our preliminary sessions established a strong foundation for future improvements to this work.